Insm1a Is Required for Zebrafish Posterior Lateral Line Development - He, Yingzi; Lu, Xiaoling; Qian, Fuping; Liu, Dong; Chai, Renjie; Li, Huawei (Frontiers in Molecular Neuroscience, 2017)
Insulinoma-associated 1 (Insm1), a zinc-finger transcription factor, is widely expressed in the developing nervous system and plays important roles in cell cycle progression and cell fate specification. However, the functions of Insm1 in the embryonic development of the sensory system and its underlying molecular mechanisms remain largely unexplored. Here, through whole-mount in situ hybridization, we found that the zebrafish insm1a gene was expressed in the posterior lateral line (pLL) system, including both the migrating pLL primordium and the deposited neuromast cells. In order to decipher the specific roles of insm1a in zebrafish pLL development, we inhibited insm1a expression by using a morpholino knockdown strategy. The insm1a morphants exhibited primordium migration defects that resulted in reduced numbers of neuromasts. The inactivation of insm1a reduced the numbers of hair cells in neuromasts, and this defect could be a secondary consequence of disrupting rosette formation in the pLL primordium. Additionally, we showed that insm1a knockdown decreased the proliferation of pLL primordium cells, which likely contributed to these pLL defects. Furthermore, we showed that loss of insm1a resulted in elevated Wnt/β-catenin signaling and downregulation of Fgf target genes in the primordium. Insm1a knockdown also perturbed the expression patterns of chemokine signaling genes. Taken together, this study reveals a pivotal role for Insm1a in regulating pLL development during zebrafish embryogenesis.